2021
DOI: 10.3389/frobt.2021.612834
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Home-Based Robotic Rehabilitation During COVID-19 Outbreak

Abstract: The coronavirus disease (COVID-19) outbreak requires rapid reshaping of rehabilitation services to include patients recovering from severe COVID-19 with post-intensive care syndromes, which results in physical deconditioning and cognitive impairments, patients with comorbid conditions, and other patients requiring physical therapy during the outbreak with no or limited access to hospital and rehabilitation centers. Considering the access barriers to quality rehabilitation settings and services imposed by socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 106 publications
(128 reference statements)
0
8
0
1
Order By: Relevance
“… [9] Drone Disinfecting contaminated objects and surfaces, broadcasting, surveillance and delivering essential products. [26] Robotics Rehabilitation [27] Drone COVID-19 screening and detection [28] Drone Contactless COVID-19 test distribution [29] Robotics Screening and evaluation of COVID-19 infections [30] Drone COVID-19 sanitization, thermal imaging [31] Robotics Surveillance, delivery, screening and prevention [32] Drone Crowd dispersal, infection monitoring, facial recognition, and logistical roles [33] Robotics Rehabilitation [34] Drone Delivery of essential products to remote areas and improving situational awareness [35] Robotics Urological cancer care during the COVID-19 crisis [36] Drone Disinfecting surfaces [37] Drone Delivery of medications and other healthcare items in COVID-19 hotspots [38] Robotics Improve testing capacity [17] Drone Medical logistics [39] Drone Dispense medicines to the COVID-19 patients [40] Robots Monitoring human temperature and people in public places [41] Drone Monitoring social distancing, disinfections and delivery of goods and medical supplies [42] Roboti...…”
Section: Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“… [9] Drone Disinfecting contaminated objects and surfaces, broadcasting, surveillance and delivering essential products. [26] Robotics Rehabilitation [27] Drone COVID-19 screening and detection [28] Drone Contactless COVID-19 test distribution [29] Robotics Screening and evaluation of COVID-19 infections [30] Drone COVID-19 sanitization, thermal imaging [31] Robotics Surveillance, delivery, screening and prevention [32] Drone Crowd dispersal, infection monitoring, facial recognition, and logistical roles [33] Robotics Rehabilitation [34] Drone Delivery of essential products to remote areas and improving situational awareness [35] Robotics Urological cancer care during the COVID-19 crisis [36] Drone Disinfecting surfaces [37] Drone Delivery of medications and other healthcare items in COVID-19 hotspots [38] Robotics Improve testing capacity [17] Drone Medical logistics [39] Drone Dispense medicines to the COVID-19 patients [40] Robots Monitoring human temperature and people in public places [41] Drone Monitoring social distancing, disinfections and delivery of goods and medical supplies [42] Roboti...…”
Section: Results Analysismentioning
confidence: 99%
“…However, due to increased hospitalization which subsequently overwhelmed healthcare systems and increased health workers’ workload, therapists could not have sufficient time to monitor the patients' progress online. To alleviate this, [26] developed an upper limb home-based robotic rehabilitation to reduce access barriers to quality rehabilitation services imposed by increased hospitalization, social distancing, stay-at-home, temporary closure of rehabilitation centers [66] and other COVID-19-related restrictions. Social distancing monitoring …”
Section: Results Analysismentioning
confidence: 99%
“…Robots can operate passively (patient-driven), actively (robot-driven), or interactively (resist the forces applied by patients) with patients [ 46 ]. Some robots have been developed specifically for home-based settings and have been successfully used to rehabilitate patients suffering from upper and/or lower extremity dysfunction [ 47 ]. By integrating robots into the telehealth patient care strategy, patients can perform robotic-assisted exercises while being remotely assessed and supervised by a therapist via an online platform.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study reported the effectiveness of a combination of TR and affordable robotic devices for home-based upper limb rehabilitation. 29 Furthermore, the addition of robotic and VR training to usual care may lead to greater improvements in the early poststroke period relative to usual care alone.…”
Section: Neurorehabilitation Devicesmentioning
confidence: 99%